Diagnóstico espacial da mobilidade e da acessibilidade dos usuários do sistema integrado de transporte de Fortaleza - Henrique, Camila Soares (2004)
Fortaleza’s Integrated Public TransitSystem (SIT-FOR), as well as other urban public transit systems inthe country, is going through a period of crisis with significant losses of its passengers in the latest years. Even facing strong competition from alternative modes, this drop in the demand isbasically associated with problems directly related to the population’s mobility, mainly the ones with the lowest incomes, who do not have the same level of accessibility to thecity and metropolitan bus systems, either due toconstantfare increases, in contrast to thereduction ofits purchasing power, and also because of the spatial configuration of the activity and transport systems. Considering such a problematic context,this research presents a methodology for diagnosing the public transit users’ mobility and accessibility spatial patterns, as well as thespatial distribution ofsocial-economic and landuse variables, candidates toexplain the phenomenon of spatial autocorrelation in the total amount of daily trips loading the system. The use of sucha methodology for analyzing the SIT-FOR, by applying exploratory spatial analysis tools in the traffic zone levels, allowed to efficiently characterize the spatial behavior of captive users’ mobility and accessibility patterns. Even dealing with the limitations of an aggregate O/D matrix, it could be concluded that the spatial analysis of the considered variables indicated a strong correlation between the users’ income and their level of system’s usage, as well asit was clearly detected thenegative effect upon mobility of users living in areas with poor transport services. It is recommended the consideration of these and other social-economic, transport and land use variables inthe development of spatial statistics confirmatory models as a means of better understanding and positively acting in the phenomenon of urban mobility.